THE IMPACT OF LEADERSHIP TRAINING THAT SERVES BY NURSING MANAGERS TOWARDS WORK MOTIVATION AND CLINICAL CARE PERFORMANCE - Junytha Ranny Rondonuwu; Asnet Leo Bunga; Wilhemus Hary Susilo (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Background: Servant Leadership is more focused on solving problems experienced by implementing nurses. The head of the room must have empathy to help them in a better direction. Aims: a study to analyze the effect of leadership training that serves the head of space on work motivation and performance of implementing nurses at GMIM General Hospital Bethesda Tomohon. Method: a quasi-experimental none equivalent pre-post test with Structural Equation Model (SEM) analysis. The number of respondents was 149 implementing nurses, in the inpatient room. Results: Research in the intervention group showed that there was an influence on the ability of the headroom, performance, and motivation of implementing nurses before and after training (p-value = 0.000). There is an influence of the level of the ability of the head of the room, work motivation, the performance of implementing nurses (p-value = 0.000) in the intervention and control groups. Structural Model test results of leadership abilities that serve significantly to the work motivation of implementing nurses with a value of t = 8.19. The effect of the level of ability of the head of space using leadership that serves significantly to the performance of implementing nurses (t = 8.13). Gender (t = 3.73), education (t = 2.81) were significant on the performance of the implementing nurses. There was a simultaneous contribution (R239%) between headroom training, age, sex, length of work on motivation and performance of implementing nurses. Conclusion: The implementation of leadership training that serves the head of the room can increase the level of knowledge of the head of the room in motivating the work and performance of implementing nurses in GMIM General Hospital Bethesda Tomohon. Suggestion: Further research on the effect of leadership training that serves long space heads and a large sample to assess behavioral changes in room heads and implementing nurses